PENGARUH KEGIATAN PEMBIASAAN KEAGAMAAN TERHADAP AKHLAK SISWA DI SMPN 7 KARAWANG BARAT - Cici Hastuti; Amirudin Amirudin; Iqbal Amar Muzaki (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
This research consists of two variables, namely religious habituation activities and student morals. This study aims to describe religious habituation activities, student morals, and the influence of both in correlational relationships. The population in this study was all students of SMPN 7 Karawang Barat and the sample amounted to 68 people. The research method used is a type of correlational research with a quantitative approach. This method is used to find the relationship between religious habituation activities and student morals. Then data collection is used with observation, questionnaires, and documentation. The distributed questionnaires were compiled using the Likert scale. Data analysis techniques use descriptive and inferential analysis. The results of this study show that habituation activities are in the low category of 12%, medium category of 72%, and high category of 16%, so it can be concluded that the average implementation of religious habituation activities is in the medium category. This means that religious habituation activities are good enough but need to be improved. Then the results of research from student morals show that student morals are in the low category of 19%, medium category of 63%, and high category of 18%, so it can be concluded that the average morals of students are in the medium category. This means that the students' morals are good enough but need to be improved again. So from the results of a simple linear regression test that gets a significance value (sig.) of 0.000 < 0.05, it can be concluded that religious habituation activities can affect student morals. The results of simple linear regression also showed the percentage of the level of influence of religious habituation activities on student morals by 46%.